2020
DOI: 10.1515/revneuro-2019-0058
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic plasticity in Alzheimer’s disease and healthy aging

Abstract: The strength and efficiency of synaptic connections are affected by the environment or the experience of the individual. This property, called synaptic plasticity, is directly related to memory and learning processes and has been modeled at the cellular level. These types of cellular memory and learning models include specific stimulation protocols that generate a long-term strengthening of the synapses, called long-term potentiation, or a weakening of the said long-term synapses, called long-term depression. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 278 publications
3
34
0
Order By: Relevance
“…Previous studies have demonstrated the close relationship between motor improvement, synaptic plasticity, and the altered expression of synaptic proteins [72][73][74]. Motor improvement is associated with the increase in the expression of presynaptic proteins [75,76].…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have demonstrated the close relationship between motor improvement, synaptic plasticity, and the altered expression of synaptic proteins [72][73][74]. Motor improvement is associated with the increase in the expression of presynaptic proteins [75,76].…”
Section: Discussionmentioning
confidence: 93%
“…How might the perturbed intercellular Ca 2+ concentration mediated by MAMs bring about neurodegeneration and cognitive deficiency in AD? Based on our examination of the relevant studies we postulate this three mechanism: First, the increased release of Ca 2+ from the ER stores in presynaptic terminals can undermine synaptic plasticity through consuming the neurotransmitters or enhancing multiple postsynaptic responses such as long-term depression (LTD) and long-term potentiation (LTP) (Figure 3ii) [82], likely leading to a negative impact on the neuronal networks and memory function [83]. Second, the sustained high levels of intracellular Ca 2+ in neurons can indirectly contribute to neuronal degeneration in AD by promoting the Aβ deposition and NFTs formation (Figure 3iii).…”
Section: Mam-mediated Calcium Homeostasis In Admentioning
confidence: 99%
“…Together, all of the above age-induced cellular alterations culminate in neuronal dysfunction, and impaired functional (i.e., synaptic) and structural neuroplasticity (including adult hippocampal neurogenesis) [ 205 , 206 , 207 , 208 , 209 ]. Indeed, in the aged brain progenitor cells exhibit several features associated with mitochondrial dysregulation, including reduced mitochondrial oxidative metabolism [ 210 ], genetic alterations that affect the functioning of the mitochondrial ETC [ 211 ], and oxidative stress.…”
Section: Metabolic and Molecular Mechanisms That Contribute To Brain Aging And Neurodegenerationmentioning
confidence: 99%